Logic and Stylistics of Irritation in Critical Studies: E. K. Herzyk and her Christian Worldview in One of the Modern Reflections - T. A. Koshemchuk (Концепт: философия, религия, культура, 2024)
The article is devoted to clarifying the logic and stylistics of the negativistic feeling, which is often the driving force behind critical research – irritation which can dictate a presupposed conclusion about the quality of work, the author's personality, and their position or worldview. Irritated criticism is characterized by simplifying and coarsening stylistics, including up to the level of direct insults. Such an approach blurs the criteria for accurate reading and blocks access to understanding. This problem is a special case in the general problem of the understanding of literary text and the methodology of its analysis. The relevance of studying this phenomenon is determined by the controversial nature of its frequent use in scientific works on cultural issues as an implicit background. The article analyzes the techniques of irritated interpretation. It is shown how the intention of denunciation generates the desire to go beyond the written text into the subtext and discover in it the author's alleged true motives, feelings and desires. At the same time, these ‘discovered motives’ inevitably become attached to the text. Some words, taken out of context and studied under the socalled psychological microscope aimed at finding evidence, are overemphasized acquiring a meaning that is not inherent in them. Further, evidentiary quotations are given selectively and in a reduced form. The article provides a number of examples of distorted interpretations using N. K. Bonetskaya’s multi-page critical reviews and studies devoted to, the writer of the Silver Age, E. K. Herzyk.  Rendered in advance, the verdict about E. Herzyk's anti-Christianity and her desire to destroy Orthodoxy in Russia logically inevitably entails the discovery of evidence of this in every manifestation of her life and work. This article aims to overcome the untruth about one of the brightest creative personalities of the Russian Silver Age, whose life and whose creative aspirations, despite the complexity of the spiritual path, unfolded in the vein of Christianity. As a result of the conducted research, the conclusion is substantiated about the need to attract the attention of the community of cultural researchers to greater methodological correctness in the process of searching for arguments that support or refute one or another point of view, taking into account the presence or absence of an ‘irritated’ approach. Furthermore, research in the field of humanitarian knowledge is associated with certain difficulties. This requires additional efforts from a serious scientist. Reflection is needed on ensuring the balance of evaluative judgments that inevitably arise when analyzing the issues under study. Even for authors recognized by the academic community, the logic and style of irritation is a challenge.